Long non-coding RNA: Functional agent for disease traits. Issue 5 (4th May 2017) - Jain, Sriyans; Thakkar, Nirav; Chhatai, Jagamohan; Pal Bhadra, Manika; Bhadra, Utpal
ABSTRACT: In recent years, long non-coding RNAs (lncRNAs) have attracted the attention of researchers with their involvement in all facets of life. LncRNAs are transcripts of more than 200 nucleotides which lack defined protein coding potential. Although they do not code for proteins, a large number of them are involved in regulating gene expression and translation. The presence of numerous lncRNAs in the human genome has prompted us to investigate the contribution of these molecules to human biology and medicine. In this review, we present the potential role of lncRNAs interlinked to different human diseases and genetic disorders. We also describe their role in cellular differentiation and aging and discuss their potential importance as biomarkers and as therapeutic agents.